Crouzons syndrome: A case report - Arathi, R; Sagtani, A; Baliga, M (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2007)
Human skull is made up of many bone joints connected by sutures. The sutures fuse in later life after the complete growth of the brain. If any of these sutures closes early, it may interfere with the normal growth of the brain. The developing brain may exert pressure on the skull and may grow in the direction of the other open sutures. Premature sutural fusion may occur alone or together with other anomalies, making up various syndromes. Crouzons syndrome is an example of such a syndrome that is associated with premature synostosis of the sutures of the skull. Presented in this article is a case of Crouzons syndrome seen in a boy aged 9 years.